Brief research report: the evolution of animal welfare legislation for pigs in 13 EU member states, 1991-2020 - Wallenbeck, Anna; Wichman, Anette; Höglind, Lisa; Agenäs, Sigrid; Hansson, Helena; Ferguson, Shon (Frontiers in Animal Science, 2024)
This brief report characterizes and maps changes in six key aspects of pig animal welfare (AW) legislation in 13 countries in the European Union (EU) during the period 1991-2020, focusing primarily on aspects of AW likely to impact the economic performance and international competitiveness of the pig production sector. National AW legislation in the selected EU member states that exceed the EU minimum levels within the six selected key areas are also mapped. Analysis of changes in AW over time, using legislative texts, academic literature, and an expert survey, revealed that AW-legislation at the national level has generally become more stringent, in line with EU directives, and that a number of member states have introduced additional AW legislation that exceed EU minimum levels. This review helps to uncover historical changes in and can form the basis for further research investigating effects of changes in AW legislation.